High‐frequency (20–50 MHz) ultrasonography of pseudoxanthoma elasticum skin lesions. (December 2013) - Guérin‐Moreau, M.; Leftheriotis, G.; Le, Y.; Etienne, M.; Amode, R.; Hamel, J.F.; Croué, A.; Le, O.; Machet, L.; Martin, L.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Typical pseudoxanthoma elasticum (PXE) skin changes are yellowish papules and are associated with unique elastic fibre fragmentation and calcification on skin biopsy. High‐frequency ultrasonography (HFUS) features of cutaneous PXE have not been reported previously. What does this study add? Noninvasive HFUS examination of the skin of patients with PXE revealed unique echostructure characteristics with oval homogeneous hypoechogenic areas in the mid‐dermis. These features may be useful for diagnosis of PXE in ambiguous cases and may aid the choice of skin site for biopsy in patients with subtle or no clinical changes. The hypoechogenic areas were consistent with the presence of localized hydration due to deposits of glycosaminoglycans.